1979
DOI: 10.1016/0003-9861(79)90421-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fasting and refeeding on the composition and synthesis of triacylglycerols, phosphatidylcholines, and phosphatidylethanolamines in rat liver

Abstract: Refeeding a high-sucrose, fat-free diet to fasted rats caused drastic alterations in the fatty acid composition of hepatic diacylglycerols, triacylglycerols, and phosphatidylcholines. However, the fatty acid profile of phosphatidylethanolamines did not change significantly. These results suggest that the fatty acid composition of diacylglycerols may influence the distribution of diacylglycerols among triacy@ycerols, phosphatidylcholines, and phosphatidylethanolamines. Fasting and refeeding also affected the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 45 publications
6
17
0
Order By: Relevance
“…Table I shows that the activity of ethanolaminephosphate cytidylyltransferase was high compared to the activity of ethanolamine kinase. This was also reported by Groener et al [22] and by Schneider and Vance [23]. On the other hand, it was shown that the activity of cholinephosphate cytidylyltransferase in rat liver is much lower than the activity of choline kinase W&'l.…”
Section: Table IIsupporting
confidence: 74%
“…Table I shows that the activity of ethanolaminephosphate cytidylyltransferase was high compared to the activity of ethanolamine kinase. This was also reported by Groener et al [22] and by Schneider and Vance [23]. On the other hand, it was shown that the activity of cholinephosphate cytidylyltransferase in rat liver is much lower than the activity of choline kinase W&'l.…”
Section: Table IIsupporting
confidence: 74%
“…207-253). In particular, CDP-choline synthesis appears to be the rate limiting step in the synthesis of phosphatidylcholine, whereas the incorporation of '4C-ethanolamine into phospholipids is not directly related to the specific activities of the enzymes involved (Groener et al, 1979). The ethanolamine pathway (Figure 7) may therefore also be regulated by the supply of substrates such as CTP or suitable diacyl glycerols (Sundler & Akesson, 1975a).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were collected, 48 h after transfection, to confirm expression of hCEPT1 using the cholinephosphotransferase activity assay. The activity was determined in the presence of exogenous DAG, as described by Groener et al [27]. At the same time point, the rate of PtdEtn synthesis was determined as described in the Incorporation of radioactive precursors into PtdEtn and PtdCho subsection.…”
Section: Transfection Of Mca-rh7777 Cells With Hcept1 Cdna Assay Of mentioning
confidence: 99%